Optimizing Shuttle Bus Paths at Mandalika Circuit with Dijkstra Algorithm to Support MotoGP Sport Tourism - Krissinta Bulan Wardhani; Rabbelia Tri Qudrani; Nafika Fatanaya; Ririn Maulidia; Sarwa Hita; M. Setyo Nugroho; Mamika Ujianita Romdhini (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2025)
Purpose: MotoGP is one of the most popular motorcycle racing events in terms of sport and recreation around the world. To get to the MotoGP venue we have to go through several routes. This route problem can disrupt visitor mobility, make them uncomfortable, and even damage the reputation of the international event. This study aims to develop a system for determining the shortest route for shuttle buses at the Mandalika Circuit by utilizing the Dijkstra algorithm. Method: To determine the shortest route we use an algorithm, one of which is the Dijkstra algorithm. The Dijkstra algorithm is one of the most well-known algorithms for finding the shortest route on a graph network. It can efficiently find the path with the minimum weight from one vertex to another. Result: The results of this study using the manual method with the contribution of the Dijkstra algorithm both produced 5 shortest routes with 2 routes in the green zone, 2 routes in the blue zone and 1 route in the red zone. Contribution: Through this analysis, a solution can be formulated for the shuttle bus route at the Mandalika Circuit in order to support sustainable MotoGP motorcycle racing tourism.